Entering the labour market in the context of higher education reform and economic recession: Young bachelor and master graduates in Portugal - Suleman, F.; Figueiredo, M. C. T. (Journal of Youth Studies, 2020)
A higher education degree has been regarded as an investment that helps young people access good jobs. However, it is increasingly difficult for young graduates to enter the labour market and, more importantly, to access high quality jobs. This paper examines determinants of the wages of young bachelor and master graduates engaged in different contractual arrangements. Linked employer-employee data, namely Quadros de Pessoal (2007 and 2011), were used to compare the impact of standard and nonstandard jobs on the wages of post-Bologna graduates who entered the labour market during the economic recession in Portugal. Most graduates start by getting a full-time job, be it stable or flexible. Empirical evidence shows wage differentials linked to the type of contractual arrangement, although the impact in 2007 is not the same in 2011. The contracts that combine flexibility with part-time work have been the most penalised in recent times. The transition of bachelors to the labour market is expected to be more precarious; however, according to data for 2011, master graduates appear to be protected against low quality jobs in Portugal.